Enzyme Biotechnology - Pearson,Annabelle (USA, 2020)
The macromolecular biological catalysts that accelerate the chemical reactions are known as enzymes. The molecules upon which enzymes react are known as substrates. These are converted into different molecules known as products. Enzymes are produced using recombinant expression in selected host microorganisms, recovery, fermentation and formulation. Enzymes are used in a variety of industries and fields such as biofuel industry, brewing industry and chemical industry. The largest user of enzymes is the detergent industry. They are utilized to remove soiling, protect garments and increase softness. Enzymes are also used in the textile, pulp and paper, leather, and animal feed industries. This book provides significant information of this discipline to help develop a good understanding of enzyme biotechnology and related fields. It aims to shed light on some of the unexplored aspects of this field. This book will serve as a valuable source of reference for graduate and post graduate students.
Keywords: Enzyme; coenzyme; Enzyme kinetics; Enzyme inhibition; Applications of EnzymeS